Confidence interval estimation of gamma distribution lifetime data using score and bootstrap methods - Larasati, Larasati; Ruswandi, Rudi; Fitriani, Fitriani (Desimal: Jurnal Matematika, 2021)
Confidence interval estimation of parameters determines the value interval, which is calculated based on statistical measurements and has specific estimates probability that contains the actual parameters. A method is needed to estimate the parameters' confidence interval, and the methods used are the Score method and the Bootstrap method. This study aims to estimate parameters by using the maximum likelihood estimation method and analyze the reliability of the aircraft engine cooling system's lifetime that follows the Gamma Distribution, and estimate the confidence interval of the parameters.